Editorial: ETHICS AND RESPONSIBILITY IN THE ‘FAKE NEWS’ TIMES - ALUAȘ, Maria (Studia Universitatis Babeş-Bolyai Bioethica, 2020)
In March 2020 the COVID-19 a pandemic was declared by the World Health Organization (WHO) representatives, and governments adopted special laws and implemented restrictions measures for population, unimaginable and incredible before. As direct consequences people reacted, buying food supplies, and advancing apocalyptic scenarios about the pandemic and the goal of official measures. Population was divides in three categories: people who consider the pandemic a war, sustained by conspiracies; people neutral, thinking that every news deserve attention, but with reserve; and people who consider that we are living a period with the Coronavirus and if they are aware about the danger, they take care of them, pandemic will end soon.